PELIBATAN PEMANGKU KEPENTINGAN LOKAL DALAM PENGEMBANGAN DAN PENGELOLAAN INTERPRETASI GEOWISATA DI KAWASAN GEOPARK DUNIA RINJANI-LOMBOK - Ruwaida Fajriasanti (Journal of Innovation Research and Knowledge, 2023)
Geo-interpretation is a form of interpretation focused on geotourism activity. It has been developed in many geotourism destinations around the world such as geoparks as an approach to bridge the meaning of geotourism resources and the visitors. In Rinjani-Lombok Geopark, geo-interpretation was first developed to help managers, local government and community in creating thematic geotourism products, through which knowledge and appreciation toward geopark’s resources can be promoted. As in other scope of tourism planning and management, the stakeholders’ involvement is vital for the success of geo-interpretation in Rinjani-Lombok Geopark. This paper attempts to examine the stakeholders and their contribution in Rinjani-Lombok Geopark’s geo-interpretation development and management. Data are gathered mainly through deep interview method with relevant individuals, and analysed qualitatively to identify actors in geo-interpretation development and their contribution in three major areas of geo-interpretation management. Result indicates that despite the effective involvement of all key actors during the planning phase, the stakeholders’ involvement has been less effective during the implementation and evaluation phase of the Geopark’s geo-interpretation. It is suggested to review challenges regarding stakeholders’ participation and contribution in the whole management process to ensure more effective and quality geo-interpretation in Rinjani-Lombok Geopark area.